Estudo da densificação e microestrutura do compósito cobregrafite preparado por moagem de alta energia e sinterizado por SPS - Nunes, Evanildo Vicente de Oliveira (2020)
Cu-graphite composite is a material used as electrical contacts. In this work, the effect of high energy milling on the production of Cu-graphite composite powders was investigated. The influence of the preparation of these powders on the densification and microstructure of the sintered samples was also the object of investigation, in addition to the effect caused on the electrical conductivity of this composite. The powders were prepared by manual mechanical mixing and high energy milling in the Pulveriseatte 7 and SPEX 8000D planetary mills. Cu powders and graphite in the proportion of 5 wt.% Of graphite were placed to milling in a Pulveriseatte 7 planetary mill with container and carbide balls and in a SPEX 8000D mill with container and stainless steel balls. In the planetary mill, the milling was carried out at 400 rpm under a high purity argon atmosphere for 50 h. During this time, samples of powders were collected after 2, 10, 20, 30 and 40 h of milling. The mass ratio of ball powder used was 1:5. The same argon atmosphere and mass ratio of powder to balls were used for milling in SPEX mill. Two powders were prepared at 400 rpm for 1 and 2 h of milling. Powder compacts prepared by milling and mechanical mixing were sintered by pulsed plasma (SPS) at 650, 700 and 950 °C for 5 minutes and under a pressure of 25, 40 and 50 MPa in a graphite cylindrical matrix and under a vacuum chamber. The heating rate used was 100°C/min. The SEM images associated with the EDS showed that the increase in the milling time caused a good dispersion and homogenization between the phases, as well as, a good refinement of the milled powders. The diffractograms revealed that the evolution of the milling promoted a reduction in the size of the crystallite in the copper phase. The sintered samples of the mixed powders showed higher density.